Legal Regulation of the Transition of Kazakhstan to Green Economy - TELEUYEV, Galym B.; KOPBASSAROVA, Gulnura K.; CHINGAYEVA, Bahtygul K.; SHERIMOVA, Nurzat Sh.; TULTABAYEV, Zulfikar Ch. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).40, 2020)
By destroying the environment, any modern society destroys its own future. For the prosperity of future generations, the environment must be preserved. To preserve nature, careful monitoring of the state of the environment, rationing and prevention of industrial emissions, development and implementation of waste-free and resource-saving technologies are required. The use of natural resources by a person with complete ignorance of the laws of nature often leads to dire, irreparable consequences. At present, humankind has begun to realize that any sector of the economy primarily affects the environment. And therefore, the world community is considering various mechanisms for preserving the environment. And of course, the idea of a green economy is one of them. A green economy is not just an opportunity, but an indispensable development path for all countries and states that aspire to ensure a reliable future for their citizens. The purpose of the study is to investigate the need and importance of the country's transition to a green economy; to research the experience of foreign countries in the transition to a green economy; to consider the ‘green economy’ as a legal phenomenon, as well as to investigate the legal issues of the transition and improvement of the regulatory framework of Kazakhstan for the transition to the green economy. The research methodology consists of materialistic dialectics, formal logical, historical law, system-analytical, comparative law and specific sociological research methods. Theoretical and practical recommendations for improving the current state mechanism for the transition to a green economy were proposed in the course of the study.